SISTEM PENDUKUNG KEPUTUSAN CALON PENERIMA DANA BANTUAN SISWA MISKIN (BSM) MENGGUNAKAN METODE MULTI-OBJECTIVE OPTIMAZION ON THE BASIS OF RATIO ANALYSIS - Abdul Rokhim; alimin al; Muchamad Lukman Hakim (SPIRIT, 2022)
Abstract :. Poor student assistance funds are assistance given to students from underprivileged families to be able to carry out learning activities at school. This assistance provides opportunities for students to pursue higher-level education.This program aims to enable students from underprivileged groups to continue their education at school. In addition, it also aims to reduce the number of students dropping out of school due to problems with education costs.Â The system used by the school still uses Microsoft Excel. In previous research, there was a system that implemented several methods to help the SMK UNTUNG SURAPATI school in determining the receipt of aid funds for poor students. To assist the SMK UNTUNG SURAPATI in selecting the recipients of funds for poor students, a web-based decision support system was created. The method used is the moora method (Multi â€“ Objective Optimization On The Basis Of Ratio Analysis). The moora method is implemented on the system to be built. The application of the moora method requires a weighting of each criterion.With the MOORA method, reports on aid funds for poor students that were previously standard and unstructured have turned into structured and directed so that the SMK UNTUNG SURAPATI schools that use this application can get a view to select students who are entitled to the assistance based on the highest score results.